2021
DOI: 10.1371/journal.pone.0250113
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of cervical cancer in Eswatini: Societal perspective

Abstract: Background Cervical cancer imposes considerable economic burden on societies and individuals. There is lack of evidence regarding this from the developing world and particularly from sub-Saharan Africa. Therefore, the study aimed to estimate the societal costs of cervical cancer in Eswatini. Materials and methods The cost of illness study (CoI) was applied using national specific clinical and registry data from hospitals, registries and reports to determine the prevalence of cervical intraepithelial neoplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Our findings are in agreement with previous studies that reported that the cost of cervical cancer mortality varied by region and country. Ngcamphalala et al ( 10 ) reported considerable costs of cervical cancer in Eswatini, with indirect costs accounting for 27% (USD5.3 million) of total expenditures and productivity loss due to premature mortality accounting for 67% (USD3.5 million). Likewise, a Vietnamese study describing the burden of colorectal cancer reported that the productivity costs of the cancer were about 83.58% of the overall cost, with 82.61% of future income loss occurring during the productive years ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in agreement with previous studies that reported that the cost of cervical cancer mortality varied by region and country. Ngcamphalala et al ( 10 ) reported considerable costs of cervical cancer in Eswatini, with indirect costs accounting for 27% (USD5.3 million) of total expenditures and productivity loss due to premature mortality accounting for 67% (USD3.5 million). Likewise, a Vietnamese study describing the burden of colorectal cancer reported that the productivity costs of the cancer were about 83.58% of the overall cost, with 82.61% of future income loss occurring during the productive years ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have described the significant economic impact of cancer in LMICs compared to high-income nations — a population-based study in 2018 about the economic impact of cervical cancer in sub-Saharan Africa reported an estimated total annual cost of cervical cancer as USD19 million ( 10 ). Likewise, the total economic cost of colorectal cancer in Vietnam was Vietnamese Dong (VND)3,041.88 billion (USD132.9 million), with indirect costs accounting for 83.58% of the total cost and 82.61% of which is future income loss ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, cancer is a leading cause of death and represents a major public health burden. According to the global cancer observatory (GLOBOCAN) report of 2018, there were an estimated 570,000 new cases of cervical cancer, with 311,000 deaths from the disease (Bray et al, 2018), mostly caused by the human papillomavirus (Ngcamphalala et al, 2021). Traditional treatments of cancer, such as chemotherapy, radiotherapy, and prophylactic vaccines have also been developed to reduce the incidence of HPV-induced cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another important success in primary prevention of cervical cancer was registered this year in Eswatini. The country is on the list of those with highest incidence of the disease in the world [3], associated with an estimated total yearly cost of 19 million USD [16]. This year, in September, the planned vaccination of 80,000 girls is due to start.…”
Section: Primary Preventionmentioning
confidence: 99%